Enteral intake of Aluminum Sulphate in acidic medium enhances absorption and alters tissue content of other trace elements in male albino rats - Hilmy, Mehdi I.; Al-Habib, Omer A. M. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: Aluminium (Al) intoxication was recognised as a causal agent in p a t i ent s undergoing haemodialysis and then was linked to Alzheimer's disease. Nevertheless, environmental pollution with Al is mainly v i a drinking water, particularly when acidic rain falls on Al containing soil and bedrock. In addition, aluminium utens i l s are widely used for cooking. Therefore, an increasing concern is emerging for the role of pH in the absorption of aluminium from ingested food.Materials and methods: The objective of this study was to establish the effect of acidification with1 ml/dL of concentrated acetic acid on the absorption of aluminium from a 5 mM a l u mi n i u m sulphate\ solution taken orally in albino rats. Levels of Al, Ca, Cu, and Fe in plasma. brain, kidney, and liver were measured by atomic absorption.Results: The results indicate that acidification of Al salt solut ion wi t h acetic acid enhances its absorption. Increased plasma Al level (p